The association between parasite infection and growth rates in Arctic charr: do fast growing fish have more parasites? - Henriksen, Eirik Haugstvedt; Smalås, Aslak; Strøm, John Fredrik; Knudsen, Rune (Hydrobiologia, 2019)
Accepted manuscript version. Final version published in Hydrobiologica, 840 (1), 261-270, is avaialble at https://doi.org/10.1007/s10750-018-3865-8. Trophically transmitted parasites are known to impair fish growth in experimental studies, but this is not well documented in natural populations. For Arctic charr [ Salvelinus alpinus (L.)], individual growth is positively correlated with food consumption. However, increased food consumption will increase the exposure to trophically transmitted parasites. Using a correlative approach, we explore the association between parasite abundance and the individual growth of Arctic charr from five lakes within the same watercourse. The studied parasite species differ in their life cycles and cost to the host. We predicted a positive association between parasite abundance and fish growth for parasites of low pathogenicity reflecting high consumption rates, and a negative association at higher parasite abundances for more costly parasites. We found no direct negative associations between parasite abundance and fish growth. The relationship between parasite abundance and growth was linearly positive for the low costly Crepidostomum sp. and concave for the more costly Eubothrium salvelini . In natural fish populations, the negative effects of parasites on fish growth might be outweighed by the energy assimilated from feeding on the intermediate host. However, experimental studies with varying food consumption regimes are needed to determine the mechanisms underlying our observations.